2018
DOI: 10.1123/smej.2017-0032
|View full text |Cite
|
Sign up to set email alerts
|

Athlete Activism and Corporate Social Responsibility: Critical Lessons From Sport Industry Professionals

Abstract: In this critical essay, 4 sport scholars discuss critical teaching points gleaned while moderating 4 concurrent roundtable discussions on the intersections of sport, corporate social responsibility, and athlete activism. The roundtable groups comprised sport industry professionals from a variety of professional teams and leagues, as well as other corporate stakeholders located in the United States and in various international locations. The purpose of this essay is to distill the roundtable discussions for uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Sport serves as an important platform for drawing attention to social issues and promoting positive social change (20,21). It largely drives discussion, debate, and dissent (22). Today, an increasing number of athletes are willing to participate in social activism.…”
Section: Social Activism Responses In Sportmentioning
confidence: 99%
“…Sport serves as an important platform for drawing attention to social issues and promoting positive social change (20,21). It largely drives discussion, debate, and dissent (22). Today, an increasing number of athletes are willing to participate in social activism.…”
Section: Social Activism Responses In Sportmentioning
confidence: 99%
“…Our methodological approach to understanding Para athlete activism was not without limitations, however. As discussed by Armstrong, Butryn, Andrews & Masucci (2018), the language in which athlete activism research is framed and discussed can be a limitation. While academics are comfortable with terms like social activism and 'future forming' approaches to research (e.g., research that aims challenge disablism and ableism), we found these 'loaded' terms and 'political' approaches are capable eliciting negative responses from athletes and sport organisations.…”
Section: Para Athlete Activism 31mentioning
confidence: 99%